Lessons Learned From Immersive and Desktop VR Training of Mines Rescuers - Pedram, Shiva; Skarbez, Richard; Palmisano, Stephen; Farrelly, Matthew; Perez, Pascal (Frontiers in Virtual Reality, 2021)
This paper discusses results from two successive rounds of virtual mines rescue training.5 The ﬁrst round was conducted in a surround projection environment (360-VR), and the second6 round was conducted in desktop virtual reality (Desktop-VR). In the 360-VR condition, trainees7 participated as groups, making collective decisions. In the Desktop-VR condition, trainees could8 control their avatars individually. Overall, 372 participants took part in this study, including 2849 mines rescuers who took part in 360-VR, and 243 in Desktop-VR. (155 rescuers experienced10 both.) Each rescuer who trained in 360-VR completed a battery of pre- and post-training11 questionnaires. Those who attended the Desktop-VR session only completed the post-training12 questionnaire. We performed principal components analysis on the questionnaire data, followed13 by a multiple regression analysis, the results of which suggest that the chief factor contributing to14 positive learning outcome was Learning Context, which extracted information about the quality of15 the learning content, the trainers, and their feedback. Subjective feedback from the Desktop-VR16 participants indicated that they preferred Desktop-VR to 360-VR for this training activity, which17 highlights the importance of task-technology ﬁt in training applications, and links back to the18 importance of Learning Context. Overall, we conclude the following: (1) it is possible to train19 effectively using a variety of technologies but technology that is well-suited to the training task20 is more useful than technology that is “more advanced,” and (2) factors that have always been21 important in training, such as the quality of human trainers, remain critical for virtual reality22 training